The racialization of sexism: men, women and gender in the populist radical right - Scrinzi, Francesca (Gender and comparative politics, 2024)
"Populist radical right (PRR) parties are questioning women's rights and sexual democracy. Yet paradoxically they appropriate issues of gender+ equality to attack the migrants and to mobilize a growing number of women as voters and members, based on a 'racialization of sexism' discourse. This book engages with these puzzling developments, in order to investigate the evolving ideologies of PRR parties and their understudied membership from a gender perspective. Why do men and women join these parties? How do they negotiate the gendered propaganda of their organizations? Do these parties mobilize their members in gender-specific ways? How is the PRR achieving growing political legitimacy through such renewed gendered ideologies? And how does its mainstreaming strategy articulate with gendered social change and the advent of new generations of activists? Drawing on a two-year comparative and intersectional study of the Lega (Nord) in Italy and the Front national (now Rassemblement national) in France, and based on over 100 activists' life histories, The Racialization of Sexism tackles how gender, at the interplay with class, ethnicity, age and religion shapes the parties' strategies as well as their activists' experiences; and how gender relations are transformed in unconventional ways within these parties. This book will be of interest to those studying gender, as well as nationalism, racism, social movements, radical politics and party politics"--